Предмет: Математика,
автор: Matvey202020
Помогите решить, пж))
А) (9 - 2(целых) 3/11) + 3(целых) 9/11 =
Б) 12(целых) 2/15 - ( 7(целых) 11/15 + 2(целых) 8/15)
Ответы
Автор ответа:
0
а) (9 - 2(целых) 3/11) + 3(целых) 9/11 =(8(целых)11/11-2( целых) 3/11)+3 (целых )9/11=6(целых)8/11+3(целых) 9/11= 9( целых) 17/11 = 10 (целых) 6/11
Похожие вопросы
Предмет: Английский язык,
автор: tshepontokozo53
Предмет: Химия,
автор: Аноним
Предмет: Английский язык,
автор: SoniZe
Предмет: Математика,
автор: nastya0151
Предмет: Математика,
автор: yana76557468418